Integrated Project Based Learning (PjBL) with STEM and Field Study in Elemental Chemistry Learning - Nurul Pratiwi; Ngatijo Ngatijo; Restina Bemis (Chempublish Journal, 2023)
This research investigates the effectiveness of a project-based learning (PjBL) model integrated with Science, Technology, Engineering, and Mathematics (STEM) in enhancing students critical thinking and field study skills in Elemental Chemistry. The study aims to assess how this integrated approach influences student learning activities, including engagement with scientific literature, teamwork, cognitive skills enhancement, and the development of teaching materials for independent discovery. A mixed-methods approach was used, combining statistical analysis of quantitative data with qualitative insights from observation sheets, interviews, and student worksheets. The curriculum included soft skill training in sampling teak sawdust (Tectona grandis) and synthesizing oxalic acid, Ca, Ba, and Mg-oxalic compounds in the lab. Results showed significant improvement in student grades in the Elemental Chemistry course, with average scores in the good category ranging from 71.05% to 79.55%, indicating the PjBL model is effective. Furthermore, the development of an Elemental Chemistry learning kit specifically designed for the PjBL approach effectively enhanced student thinking skills, as evidenced by their achievements in STEM-related tasks, highlighting the potential of integrated learning method in improving educational outcomes in higher education chemistry courses.